2016
DOI: 10.1177/0743558416637425
|View full text |Cite
|
Sign up to set email alerts
|

Helping Parents With Chores or Going Out With Friends: Cultural Differences in Adolescents’ Responses to Potentially Conflicting Expectations of Parents and Peers

Abstract: The study examined cultural similarities and differences in how adolescents deal with conflicting expectations of parents and peers. It was tested to what extent adolescents' interdependence values and satisfaction with family and friendships predict the way they would solve the disagreement, where they had planned to go out with friends, but their parents wanted them to stay at home to do chores. Moreover, adolescents' reasons for their reported actions were examined. The sample included 894 Estonian, German,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Negotiation together with self‐oriented interests might, however, also be an indication of manipulation, whereby adolescents secretly follow their own wishes. A recent study found similarly that adolescents from Estonia and Germany – individualistic cultures – sometimes suggested compliance in hypothetical parent‐adolescent disagreement for self‐oriented reasons (Tamm et al, 2017). Current and previous findings thus point out the importance of examining both strategies and reasons of adolescents.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Negotiation together with self‐oriented interests might, however, also be an indication of manipulation, whereby adolescents secretly follow their own wishes. A recent study found similarly that adolescents from Estonia and Germany – individualistic cultures – sometimes suggested compliance in hypothetical parent‐adolescent disagreement for self‐oriented reasons (Tamm et al, 2017). Current and previous findings thus point out the importance of examining both strategies and reasons of adolescents.…”
Section: Discussionmentioning
confidence: 93%
“…Research on parent‐child conflicts has, however, shown the importance of examining both the strategies and the reasons. Adolescents' reasons are likely to reflect more strongly their attitudes and goals than their strategies (Phinney, Kim‐Jo, Osorio, & Vilhjalmsdottir, 2005; Tamm, Kasearu, Tulviste, Trommsdorff, & Saralieva, 2017). It has been found that adolescents sometimes use, for example, compliance for self‐oriented reasons (Tamm et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…коллектив кафедры общей социологии и социальной работы под руководством профессора З. Х.-М. Саралиевой включился в масштабный социологический проект «Value of Children and Intergenerational Relationships» (VoC), посвященный изучению и кросс-культурному анализу ценности детей и межпоколенных отношений [Tamm et al, 2017;Саралиева, Балабанов, 2009;Балабанов, 2009]. Концептуальной основой для исследования стал подход Ч. Катчибаши, выделившей три основных аспекта ценности детей, актуальных для конкретных обществ и в макросоциологической перспективе определяющих репродуктивные стратегии их членов [Kagitcibasi, 1982].…”
unclassified